Mind your step: predicting maximum ankle inversion during cutting movements in soccer - Miller, P.; Brinkmann, D. J.; Ramsenthaler, C.; Gollhofer, A.; Gehring, D. (Sports Biomechanics, 2024)
The objective of this investigation was to identify parameters at initial contact that would predict the subsequent maximum ankle inversion angle during cutting movements. We conducted a secondary data analysis and calculated kinematics of 1,400 cuttings performed by 46 male soccer athletes. The movement task consisted of an approach run, followed by a pre-planned cutting movement. A linear mixed regression model was applied to predict the maximum ankle inversion angle during the first 100ms of ground contact. The prediction was made based on six predictors that describe change-of-direction intensity and foot placement as found to be relevant in the literature. The model explained 62% of the variance of maximum ankle inversion angles. A change of the main predictors (foot rotation, cutting angle and initial ankle inversion) by 1 SD caused a reduction of the subsequent maximum ankle inversion angle by 2.6-4.4°. Regarding the intensity of a change-of-direction movement, cutting angle seems to have a higher influence on maximum ankle inversion angle than approach velocity. With respect to the individual foot positioning, the maximum ankle inversion angle can be reduced by increasing exorotation and eversion of the foot while shifting towards forefoot landing.